2015
DOI: 10.1523/jneurosci.2493-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Occipital Face Area Is Causally Involved in Facial Viewpoint Perception

Abstract: Humans reliably recognize faces across a range of viewpoints, but the neural substrates supporting this ability remain unclear. Recent work suggests that neural selectivity to mirror-symmetric viewpoints of faces, found across a large network of visual areas, may constitute a key computational step in achieving full viewpoint invariance. In this study, we used repetitive transcranial magnetic stimulation (rTMS) to test the hypothesis that the occipital face area (OFA), putatively a key node in the face network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…While the VWFA result is consistent with existing models and experimental findings (Cohen et al, 2003; Molko et al, 2002), including finding from fMRI repetition suppression (Glezer, Jiang, & Riesenhuber, 2009), our observation of the same effect in the OWFA suggests that inter-hemifield integration of word form information occurs outside of the VWFA, and possibly during an earlier pre-lexical stage of shape processing than predicted by existing models of whole-word representation in the visual system. Interestingly, a similar proposal has been offered recently to explain right-lateralized face processing (Frässle et al, 2016), which exhibits striking parallels with word recognition (Behrmann & Plaut, 2013; Dehaene et al, 2015; Dundas, Plaut, & Behrmann, 2012), especially with respect to symmetry processing (Bona et al, 2015; Kietzmann et al, 2015), which may have a parallel in the OWFA for “symmetry breaking” in visual word form processing (possibly in addition to the VWFA; Pegado, Nakamura, Cohen, & Dehaene, 2011). Furthermore, given that defective callosal transfer and inter-hemispheric coordination is associated with dyslexia (Fabbro et al, 2001; Henderson et al, 2007), our findings highlight the possibility that at least some cases of dyslexia may be the result of impaired inter-hemifield integration (Kelly, Jones, McDonald, & Shillcock, 2004).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…While the VWFA result is consistent with existing models and experimental findings (Cohen et al, 2003; Molko et al, 2002), including finding from fMRI repetition suppression (Glezer, Jiang, & Riesenhuber, 2009), our observation of the same effect in the OWFA suggests that inter-hemifield integration of word form information occurs outside of the VWFA, and possibly during an earlier pre-lexical stage of shape processing than predicted by existing models of whole-word representation in the visual system. Interestingly, a similar proposal has been offered recently to explain right-lateralized face processing (Frässle et al, 2016), which exhibits striking parallels with word recognition (Behrmann & Plaut, 2013; Dehaene et al, 2015; Dundas, Plaut, & Behrmann, 2012), especially with respect to symmetry processing (Bona et al, 2015; Kietzmann et al, 2015), which may have a parallel in the OWFA for “symmetry breaking” in visual word form processing (possibly in addition to the VWFA; Pegado, Nakamura, Cohen, & Dehaene, 2011). Furthermore, given that defective callosal transfer and inter-hemispheric coordination is associated with dyslexia (Fabbro et al, 2001; Henderson et al, 2007), our findings highlight the possibility that at least some cases of dyslexia may be the result of impaired inter-hemifield integration (Kelly, Jones, McDonald, & Shillcock, 2004).…”
Section: Discussionsupporting
confidence: 55%
“…The OFA is typically larger and more frequently found in the right hemisphere (Pitcher, Walsh, & Duchaine, 2011), and it represents visual features of faces and spatial relations between them during the early stages of processing (Liu, Harris, & Kanwisher, 2010; Pitcher, Walsh, Yovel, & Duchaine, 2007; Rhodes, Michie, Hughes, & Byatt, 2009; Strother et al, 2011). The right OFA is distinct from its more elusive left counterpart in its sensitivity to mirror and its role in interhemispheric integration during face recognition (Bona, Cattaneo, & Silvanto, 2015; Frässle et al, 2016; Kietzmann et al, 2015). …”
Section: Introductionmentioning
confidence: 90%
“…We also observed a gaze representation in the right STS that were discriminative of differences in gaze direction. These findings are consistent with those of previous studies Axelrod & Yovel, 2012;Duchaine & Yovel, 2015;Haxby et al, 2000;Kietzmann et al, 2012Kietzmann et al, , 2015.…”
Section: Neural System For Perception Of Facessupporting
confidence: 94%
“…Analysis involved comparing differences in the amplitude of brain responses and/or the use of multi-voxel pattern analysis (MVPA) to reveal the mechanisms underlying the processing of face-related data by the human brain. Experiment results reported by (Allison, Puce, & McCarthy, 2000;Axelrod & Yovel, 2012;Haxby et al, 2000;Kietzmann et al, 2012Kietzmann et al, , 2015 indicate that the inferior occipital gyri or occipital face area (OFA) is involved in the early perception of face viewpoint, whereas the superior temporal sulcus (STS) deals with movements in the eyes and mouth. Investigations into the temporal stages of face perception using EEG/MEG have indicated that the N170/M170 component is an event-related potential/field, which occurs approximately 170 ms after the stimulus onset and appears to originate in the fusiform face area (FFA) or STS (Deffke et al, 2007;Duchaine & Yovel, 2015;Nguyen & Cunnington, 2014;Sadeh, Podlipsky, Zhdanov, & Yovel, 2010).…”
mentioning
confidence: 99%
“…Several TMS studies have demonstrated how the OFA is causally engaged in processing low level facial features. For example, Kietzmann et al (2015) demonstrated that TMS delivered over the right OFA impaired judgments of viewpoint angle when faces were presented in the contralateral (but not the ipsilateral) visual field. The same study also demonstrated that TMS delivered over the right OFA impaired judgements of facial viewpoint symmetry in both visual fields.…”
Section: Tms Studies Of Face Perception In the Ofamentioning
confidence: 99%